PACAP and VIP Inhibit the Invasiveness of Glioblastoma Cells Exposed to Hypoxia through the Regulation of HIFs and EGFR Expression - Maugeri, Grazia; Grazia D’Amico, Agata; Reitano, Rita; Magro, Gaetano; Cavallaro, Sebastiano; Salomone, Salvatore; D’Agata, Velia (Frontiers in Pharmacology, 2016)
Pituitary adenylate cyclase-activating polypeptide (PACAP) and vasoactive intestinal peptide (VIP) through the binding of vasoactive intestinal peptide receptors (VIPRs), perform a wide variety of effects in human cancers, including glioblastoma multiforme (GBM). This tumor is characterized by extensive areas of hypoxia, which triggers the expression of hypoxia-inducible factors (HIFs). HIFs not only mediate angiogenesis but also tumor cell migration and invasion. Furthermore, HIFs activation is linked to epidermal growth factor receptor (EGFR) overexpression. Previous studies have shown that VIP interferes with the invasive nature of gliomas by regulating cell migration. However, the role of VIP family members in GBM infiltration under low oxygen tension has not been clarified yet. Therefore, in the present study we have investigated, for the first time, the molecular mechanisms involved in the anti-invasive effect of PACAP or VIP in U87MG glioblastoma cells exposed to hypoxia induced by treatment with desferrioxamine (DFX). The results suggest that either PACAP or VIP exert an anti-infiltrative effect under low oxygen tension by modulating HIFs and EGFR expression, key elements involved in cell migration and angiogenesis. These peptides act through the inhibition of PI3K/Akt and MAPK/ERK signaling pathways, which are known to have a crucial role in HIFs regulation. In conclusion, the modulation of hypoxic event and the anti-invasive effect exerted by some VIP family members might open new insights in the therapeutic approach to GBM.